Advanced application of porcine intramuscular adipocytes for evaluating anti-adipogenic and anti-inflammatory activities of immunobiotics. - Masahiko Suzuki; Asuka Tada; Paulraj Kanmani; Hitoshi Watanabe; Hisashi Aso; Yoshihito Suda; Tomonori Nochi; Kenji Miyazawa; Kazutoyo Yoda; Fang He; Masataka Hosoda; Tadao Saito; et al. (PLoS ONE, 2015)
We previously established a clonal porcine intramuscular preadipocyte (PIP) line and we were able to establish a protocol to obtain functional mature adipocytes from PIP cells. We hypothesized that both PIP cells and mature adipocytes are likely to be useful in vitro tools for increasing our understanding of immunobiology of adipose tissue, and for the selection and study of immunoregulatory probiotics (immunobiotics) able to modulate adipocytes immune responses. In this study, we investigated the immunobiology of PIP cells and mature adipocytes in relation to their response to TNF-α stimulation. In addition, we evaluated the possibility that immunobiotic microorganisms modify adipogenesis and immune functions of porcine adipose tissue through Peyer's patches (PPs) immune-competent cells. We treated the porcine PPs immune cells with different probiotic strains; and we evaluated the effect of conditioned media from probiotic-stimulated immune cells in PIP cells and mature adipocytes. The Lactobacillus GG and L. gasseri TMC0356 showed remarkable effects, and were able to significantly reduce the expression of pro-inflammatory factors and negative regulators (A20, Bcl-3, and MKP-1) in adipocytes challenged with TNF-α. The results of this study demonstrated that the evaluation of IL-6, and MCP-1 production, and A20 and Bcl-3 down-regulation in TNF-α-challenged adipocytes could function as biomarkers to screen and select potential immunobiotic strains. Taking into consideration that several in vivo and in vitro studies clearly demonstrated the beneficial effects of Lactobacillus GG and L. gasseri TMC0356 in adipose inflammation, the results presented in this work indicate that the PIP cells and porcine adipocytes could be used for the screening and the selection of new immunobiotic strains with the potential to functionally modulate adipose inflammation when orally administered.